Direito fundamental ao juiz natural : o sentido da norma e a visão do STF, no HC 96.821 - França, Daiane Sabbag David (2023)
The objective of this study is to examine whether the concept of the rule of law regarding the natural judge is being understood and respected by the Supreme Court, specifically focusing on the decision made in the Habeas Corpus 96.821 case, which has been replicated to the present day. The theoretical framework centers on the notion of due process of law as a fundamental guarantee within the current Democratic Rule of Law, recognized both constitutionally and internationally. To arrive at a comprehensive answer, the analysis considers the prerequisites for safeguarding the core protection of this right, starting with the requirement that the legal doctrine applied in the field of decision-making is compatible with the Brazilian legal system, which prioritizes fundamental rights. Additionally, it investigates the origins of the norm of the natural judge as a guiding principle for other fundamental rights within the legal process, particularly freedom and equality. Lastly, it delves into an examination of the arguments presented in the decision, which suggests that first-instance judges can act as if they were appellate judges, deviating from the prescribed legal criteria. The historiography found in documents dating back to the decades preceding the French Revolution, along with the relevant scholarly works of that era and subsequent years, have significantly contributed to this research. Together with the protective provisions at the universal, regional, and local levels, these sources have enabled a thorough analysis of the reasoning behind the decision rendered in the HC 96,821 case and the underlying principles expressed therein. The findings indicate that the formulation of the reasoning leading to the decision in question was conducted in disregard of due process of law, resulting in a failure to uphold the concept of the natural judge and consequent violation thereof.